Structure Parameters of Synaptic Vesicles Quantified by Small-Angle X-Ray Scattering - Castorph, Simon (The Biophysical Society, 2010)
Synaptic vesicles (SVs) are small, membrane-bound organelles that are found in the synaptic terminal of neurons, and which are crucial in neurotransmission. After a rise in internal [Ca(2+)] during neuronal stimulation, SVs fuse with the plasma membrane releasing their neurotransmitter content, which then signals neighboring neurons. SVs are subsequently recycled and refilled with neurotransmitter for further rounds of release. Recently, tremendous progress has been made in elucidating the molecular composition of SVs, as well as putative protein-protein interactions. However, what is lacking is an empirical description of SV structure at the supramolecular level—which is necessary to enable us to fully understand the processes of membrane fusion, retrieval, and recycling. Using small-angle x-ray scattering, we have directly investigated the size and structure of purified SVs. From this information, we deduced detailed size and density parameters for the protein layers responsible for SV function, as well as information about the lipid bilayer. To achieve a convincing model fit, a laterally anisotropic structure for the protein shell is needed, as a rotationally symmetric density profile does not explain the data. Not only does our model confirm many of the preexisting ideas concerning SV structure, but also for the first time, to our knowledge, it indicates structural refinements, such as the presence of protein microdomains.